2008
DOI: 10.1897/07-462.1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary uptake models used for modeling the bioaccumulation of organic contaminants in fish

Abstract: Numerous models have been developed to predict the bioaccumulation of organic chemicals in fish. Although chemical dietary uptake can be modeled using assimilation efficiencies, bioaccumulation models fall into two distinct groups. The first group implicitly assumes that assimilation efficiencies describe the net chemical exchanges between fish and their food. These models describe chemical elimination as a lumped process that is independent of the fish's egestion rate or as a process that does not require an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 163 publications
(328 reference statements)
1
52
0
Order By: Relevance
“…Although studies of allometric scaling in fish are complicated by confounding influences of temperature, pH, and other factors, numerous studies have shown that intraspecific metabolic rate (measured as resting oxygen consumption) tends to scale to a fractional exponent of body weight, typically ranging from 0.6 to 0.9 when expressed on a whole-animal basis [42][43][44][45][46][47][48]. Allometric relationships containing similar exponents also figure prominently in many published models for chemical accumulation by fish, reflecting assumed or characterized relationships between fish size and biological determinants of chemical flux, including gill ventilation volume, cardiac output, food consumption rate, and absorptive surface area [49][50][51].…”
Section: Discussionmentioning
confidence: 95%
“…Although studies of allometric scaling in fish are complicated by confounding influences of temperature, pH, and other factors, numerous studies have shown that intraspecific metabolic rate (measured as resting oxygen consumption) tends to scale to a fractional exponent of body weight, typically ranging from 0.6 to 0.9 when expressed on a whole-animal basis [42][43][44][45][46][47][48]. Allometric relationships containing similar exponents also figure prominently in many published models for chemical accumulation by fish, reflecting assumed or characterized relationships between fish size and biological determinants of chemical flux, including gill ventilation volume, cardiac output, food consumption rate, and absorptive surface area [49][50][51].…”
Section: Discussionmentioning
confidence: 95%
“…fed copepods (Reinfelder and Fisher 1994). Dietary uptake models for organic contaminants in fish have been reviewed by Barber (2008), where assimilation efficiencies ranged from 40% to 100%. Assimilation efficiencies of chemicals must be distinguished from assimilation efficiencies of food components such as lipids.…”
Section: Toxicokineticsmentioning
confidence: 99%
“…For example, even the fundamentals of how different types of circulatory systems, presence or absence of barriers separating the site of action from the rest of the organism, or characteristics of specific organs affect the distribution of contaminants are unknown. Once further relevant traits and their relationship to internal distribution are identified, these may be linked to pharmacokinetic models, such as the physiologically-based pharmacokinetic (PBPK) and adsorption distribution metabolism excretion (ADME) models (Barber 2008) or dynamic energy budget models (DEB) (Kooijman and Bedaux 1996), which are well developed for some model systems but are rarely applied to nonmodel species because of their high data demand. In contrast, processes of active biological transport may be very suitable to incorporate into these types of models.…”
Section: Toxicokineticsmentioning
confidence: 99%
“…For model applications, G Feed is obtained from a bioenergetics submodel and may be variable over time [13,14]. The dietary AE is chemical specific and considered to be a constant under thermodynamic model formulations that consider dietary uptake and fecal egestion as separate processes [12]. However, empirical measurements demonstrate considerable variability in the magnitude of AE (20 to >90%) across different studies and diet types [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%